2021
DOI: 10.3389/fphys.2021.732709
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Ovarian Hyperstimulation Protocol in Infertile Patients During the COVID-19 Pandemic

Abstract: Objectives: To explore the appropriate controlled ovarian hyperstimulation (COH) protocols in infertility patients who received the in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) treatments during the COVID-19 pandemic.Materials and Methods: This retrospective cohort study evaluated the efficiency of the early follicular-phase long-acting GnRH-agonist long (EFLL) protocol (a new protocol developed by Chinese clinicians), prolonged pituitary down-regulation of EFLL protocol (Pro-EFLL), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Similarly, there are contradictory findings regarding the effect of COVID‐19 on serum testosterone levels. Some studies have suggested a decrease in testosterone levels after COVID‐19, 14,35 while others have found no postillness changes in testosterone levels 13,37 . Histopathological changes in testicular tissue following COVID‐19 have been proven with many autopsy samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there are contradictory findings regarding the effect of COVID‐19 on serum testosterone levels. Some studies have suggested a decrease in testosterone levels after COVID‐19, 14,35 while others have found no postillness changes in testosterone levels 13,37 . Histopathological changes in testicular tissue following COVID‐19 have been proven with many autopsy samples.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested a decrease in testosterone levels after COVID-19, 14,35 while others have found no postillness changes in testosterone levels. 13,37 Histopathological changes in testicular tissue following COVID-19 have been proven with many autopsy samples. These studies have shown degeneration in testicular tissue and germ cells, 11 damage to seminiferous tubule cells, lymphocytic inflammation, decrease in Leydig cells, 12,38 increase in the number of apoptotic cells, macrophage infiltration, 29,39 decreased spermatogenesis, and Although there is controversy regarding the histopathological and hormonal changes associated with SARS-CoV-2 infection, existing literature suggests that semen parameters may be adversely affected following infection.…”
Section: Discussionmentioning
confidence: 99%